Desenvolvimento de uma metodologia fuzzy, aplicada no modelo da onda difusa, para estudar o comportamento da propagação de ondas de cheias, em funções de parâmetros hidráulicos nas suas formas fuzzys - Castro, Maria Patrícia Sales (2015)
Many of the problems which involve hydrodynamic wave propagation along the extension in natural channels are resolved through the Saint-Venant equation. In most the wave propagation channels practical applications in natural terms of inertia are neglected, so the Saint-Venant equation system is reduced to an equation satellite, known as the diffusive wave equation. This research aims apply the Fuzzy theory to model the propagation of diffused wave in natural channels in order to check the uncertainties related to the hydrodynamic parameters present in these models. Through the Finite Difference Method Implicit differential equations were solved Partial in a fuzzy way. To carry out a set of simulations for the most different scenarios in the water body was developed a computer program, in language FORTRAN. The results show that the behavior of wave propagation diffusive suffers strong influence of hydraulic parameters, slope and number of Manning. According to the presented results, it was concluded that the application of Fuzzy Theory in hydrodynamic systems, evaluation of uncertainty is a viable alternative to determining the risk of flooding and thus be more a support tool in Water Resources Management programs